Nutritional dynamics during the development of xylophagous beetles related to changes in the stoichiometry of 11 elements. (30th September 2016) - Filipiak, Michał; Weiner, January
Abstract: The present study examines the adaptive strategy used by wood‐boring beetles to compensate for the lack of nutrients in dead wood. The contents of nutritional elements in growing wood‐boring beetles ( Stictoleptura rubra L. and Chalcophora mariana Dejean) are compared with the elemental composition of decaying dead wood (pine stumps), showing changes during the beetles' ontogenetic (i.e. larval) development. The stoichiometric ratios of C and other nutritional elements (N, P, K, Na, Ca, Mg, Fe, Zn, Mn and Cu) are investigated to identify the most important nutrients for larval development. The degree of nutritional mismatch that is encountered by the beetle larvae changes dramatically over 3–4 years of simultaneous larval growth and wood decay. Excluding C, the relative contents of nutritional elements increase substantially in decaying wood, whereas the opposite tendency is found in larvae, most likely because of carbon deposition in fat. The elements limiting larval development because of their scarcity in dead wood are N, P, K, Na, Mg, Zn and Cu. Fungal activity (i.e. the transport of nutrients from the surrounding environment to decaying stumps) can explain the observed mitigation of the original mismatch, although prolongation of the larval development time is still necessary to compensate for the scarcity of some of the required elements in food.